2023
DOI: 10.1021/acs.jafc.3c02454
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Novel Umami Peptides from Protein Hydrolysates of Morchella esculenta and Their Interaction with T1R1/T1R3 Receptor

Xuefeng Wang,
Dan Zhang,
Qihong Guo
et al.

Abstract: The study aimed to explore umami peptides derived from protein hydrolysates of Morchella esculenta. According to the electronic tongue and sensory evaluation, the ultrafiltration fractions (<3 kDa) of the protein hydrolysates exhibited the strongest umami taste. The overall flavor of the screened fractions was significantly improved after the Maillard reaction, based on the electronic nose and electronic tongue analyses, and the content of total free amino acid increased from 387.35 to 589.30 μg/mL. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
(98 reference statements)
0
0
0
Order By: Relevance
“…These findings indicate that the model was satisfactory, as over 90% of the points were found within the reasonable regions, and amino acid residues conserved a better conformational configuration. 7 In addition, the final active conformation of the heterodimer obtained in our study showed consistency with the modeling results obtained by Zhang et al 38 and Wang et al 39 Therefore, the above findings showed that the homology models possessed high reliability, which was then employed in molecular docking analysis.…”
Section: Resultssupporting
confidence: 90%
“…These findings indicate that the model was satisfactory, as over 90% of the points were found within the reasonable regions, and amino acid residues conserved a better conformational configuration. 7 In addition, the final active conformation of the heterodimer obtained in our study showed consistency with the modeling results obtained by Zhang et al 38 and Wang et al 39 Therefore, the above findings showed that the homology models possessed high reliability, which was then employed in molecular docking analysis.…”
Section: Resultssupporting
confidence: 90%